A comparison between the life cycle cost of gravel and of bituminous surfacing options for feeder roads in Ghana. Issue Volume 18:Issued 3(2017) (4th March 2017) - Ampadu, Samuel Innocent Kofi; Addison, Frederick Kwamina
Abstract : Feeder roads, which constitute a key component of rural transport infrastructure, play a vital role in rural development, but only 5% of the total feeder road network in Ghana has bituminous seal surfacing. The remaining 95% have either gravel or earth surfacing. However, gravel surfacing (G-S) is known to deteriorate rather rapidly necessitating expensive frequent maintenance while bituminous surfacing offers a more durable surfacing. Various life cycle cost studies have suggested that even though G-S may have lower initial construction costs, they tend to have higher life cycle costs than bituminous seal surfaced ones. However, since most of these studies are based on ideal maintenance practices, their conclusions do not reflect actual field conditions. This study seeks therefore to compare the life cycle cost of G-S with that of bituminous seal surfacing options for engineered feeder roads in Ghana using actual cost data. Data were collected from eight feeder road projects with G-S and a similar number with bituminous surfacing from six regions of Ghana completed between 2010 and 2013. The life cycle cost for each road was computed using a discount rate of 12% and an inflation rate of 15% over an analysis period of 21 years. The results for G-S are then compared with those for single bituminous seal surfacing and for double bituminous seal surfacing. The results are further compared with those from trial sections of an experimental study of Otta seal surfacing using natural gravel and using crushed rock as aggregates. The results suggest that based on the high initial construction costs of bituminous seal surfacing and actual low maintenance intervention practices, G-S remain the least cost option. The study recommends the need for alternative surfacing technology that does not involve bitumen.